#### Answer

$\dfrac{\dfrac{3}{4}-\dfrac{1}{2}}{\dfrac{3}{8}+\dfrac{1}{6}}=\dfrac{6}{13}$

#### Work Step by Step

$\dfrac{\dfrac{3}{4}-\dfrac{1}{2}}{\dfrac{3}{8}+\dfrac{1}{6}}$
Evaluate the substraction indicated in the numerator and the sum indicated in the denominator:
$\dfrac{\dfrac{3}{4}-\dfrac{1}{2}}{\dfrac{3}{8}+\dfrac{1}{6}}=\dfrac{\dfrac{3-2}{4}}{\dfrac{9+4}{24}}=\dfrac{\dfrac{1}{4}}{\dfrac{13}{24}}=...$
Evaluate the division and simplify:
$...=\dfrac{1}{4}\div\dfrac{13}{24}=\dfrac{24}{4(13)}=\dfrac{6}{13}$